Body composition, power muscle, and baropodometric assessment in elite Muay Thai athletes - Quintero, M. A.; Fuentes-Garcia, J. P.; Poblete-Valderrama, F.; Pereira de Andrade, G. A.; De la Rosa, A. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2024)
Background. Muay Thai is a dynamic fighting style which has existed for over 2000 years and consists of using a multitude of fists, kicks, and knee and elbow strikes to knock out the opponent. Studies indicate that the general physiologic profile of Muay Thai athletes is high anaerobic power and muscular strength, with low body fat percentage and a mesomorphic somatotype.